Model Pemanfaatan Bersama Sumber Mata Air Sebagai Common Property oleh Masyarakat di Desa Cikahuripan Kecamatan Cimanggung Kabupaten Sumedang - Desi Yunita; Novie Indrawati Sagita (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
Common property as a model of common ownership of natural resources is very likely to be a common tragedy if social conditions are not prepared in such a way as to maintain the sustainability of the shared use of water resources. The purpose of this research is to know the model of joint utilization of springs by society. Whether the model of joint utilization done so far can have an impact on the destruction of the springs or vice versa. This research is using qualitative approach and case study method, data is ollected directly and natural (real life events) through observation, interview, focus group discussion, and location search. The results were analyzed using the structural funcional theory and the concept of common property. The results show that although the community continues to grow but the utilization of water sources together is maintained. The existence of efforts to capitalize the source of the springs also still consider the aspect of needs and benefits for the community where the springs are located. Still maintaining the model of joint utilization of this spring can not be separated from social ties among members of the community, so the sustainability is still maintained